Motion Control for Nonholonomic Wheeled Mobile Robots with Obstacle Avoidance - Tran, Luc Quan (Curtin University, 2019)
Wheeled mobile robot finds various applications because it can perform tasks autonomously in dangerous environments. Controlling this system has become active because of both challenges in applied nonlinear control theory and practical importance. This research aims to deploy nonlinear control strategies to solve two problems: path tracking and obstacle avoidance. The research extends the recent works to the scenario where collision avoidance between the robot and obstacles, and constraints in the control inputs are considered.